Both Hypoxia-Inducible Factor 1 and MAPK Signaling Pathway Attenuate PI3K/AKT via Suppression of Reactive Oxygen Species in Human Pluripotent Stem Cells - Fojtík, Petr; Beckerová, Deborah; Holomková, Katerina; Šenfluk, Martin; Rotrekl, Vladimir (Frontiers in Cell and Developmental Biology, 2021)
Mild hypoxia (5% O2) as well as FGFR1-induced activation of PI3K/AKT and MAPK signaling pathways markedly support pluripotency in human pluripotent stem cells (hPSCs). This study demonstrates that the pluripotency-promoting PI3K/AKT signaling pathway is surprisingly attenuated in mild hypoxia compared to the 21% O2 environment. Hypoxia is known to be associated with lower levels of reactive oxygen species (ROS), which are recognized as intracellular second messengers capable of upregulating the PI3K/AKT signaling pathway. Our data denote that ROS downregulation results in pluripotency upregulation and PI3K/AKT attenuation in a hypoxia-inducible factor 1 (HIF-1)-dependent manner in hPSCs. Using specific MAPK inhibitors, we show that the MAPK pathway also downregulates ROS and therefore attenuates the PI3K/AKT signaling – this represents a novel interaction between these signaling pathways. This inhibition of ROS initiated by MEK1/2-ERK1/2 may serve as a negative feedback loop from the MAPK pathway toward FGFR1 and PI3K/AKT activation. We further describe the molecular mechanism resulting in PI3K/AKT upregulation in hPSCs - ROS inhibit the PI3K’s primary antagonist PTEN and upregulate FGFR1 phosphorylation. These novel regulatory circuits utilizing ROS as second messengers may contribute to the development of enhanced cultivation and differentiation protocols for hPSCs. Since the PI3K/AKT pathway often undergoes an oncogenic transformation, our data could also provide new insights into the regulation of cancer stem cell signaling.